Exploring the practices of secondary school teachers in preparing for classroom observation amidst the new normal of education - Caratiquit, Kevin; Pablo, Reynel (Goodwood Publishing, 2021)
Purpose: This study aimed to explore the practices of secondary public school teachers in preparing for classroom observation amidst the new normal of education. The emphasis of this study was drawn from the central question,